Ethical principles in Nizam Al-Mulk's Siyasatnama book in terms of Turkish management history - Süleyman Göksoy (Journal of Pedagogical Research, 2017)
The aim of the present research is to explain the ethical principles of management in Nizam al-Mulk's Siyasatnama book in terms of Turkish management history and to investigate the contributions of managerial ethical principles in Siyasatnama to Turkish management field. The main resource of the research is Nizam al-Mulk's Siyasatnama treatise. As the method, the research is a theoretical study based on literature. Nizam al-Mulk's Siyasatnama book has been regarded as the major managerial work, therefore it was examined with the data collection tool and ethical principles related to the topic were gathered. Research data consist of Nizam al-Mulk's managerial book named Siyasatnama and ethical principles of management mentioned in Siyasatnama. Besides, interpretations and academic studies carried out on Siyasatnama were consulted. Written materials which were taken as the basis of the research were analyzed by using content analysis method. The main reason why the content of  Siyasatnama book was analyzed is to explain the obtained data and to determine their relationship with the prominent notions. The ethical principles of management mentioned in Siyasatnama book were determined as the main category of the research.